Study of Image steganography using LSB, DFT and DWT - Mazumder, Juned Ahmed; Hemachandran, K. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper we have studied and implement the color image steganography using LSB, DFT and DWT. First we have studied the various literatures of LSB, DFT and DWT and then implemented one system in which we can do steganography using these techniques, after implementation we have evaluated the results using these techniques applying various image formats against different message size. For each of the cases we have calculated Â the MSE and PSNR and presented here in a tabulated form. Our main intention is to show how MSE and PSNR changes with respect to different image formats and different message sizes using these techniques. Besides the analysis of MSE and PSNR we have also analyzed the message insertion and message extraction time for all the cases.